Analisis Variabel yang Mempengaruhi Minat Investasi Berbasis Aplikasi - Lina Affifatusholihah; Solehatin Ika Putri (University of Merdeka Malang, 2021)
This study considers how the direct and indirect impact from variable of advertising attitude, brand awareness, brands attitude to interest in using online investment applications. Quantitative method for data analysis using SEM Warp PLS 7.0 application with a sample of 103 people. The results of the study stated that advertising attitude had no effect on brands attitude, brand awareness had a significant positive effect on brands attitude. Brands attitude have an effect on interest in using online investment applications. Advertising attitudes have an effect on interest in using online investment applications. Brand awareness have an effect on interest in using online investment applications. Brands attitude cannot mediate the effect of advertising attitude on interest in using online investment applications. Brands attitude mediate the effect of brand awareness on interest in using online investment applications. Conclusion in this study stated that variable of advertising attitude, brand awareness, brands attitude had direct effect to interest in using online investment applications. In addition, brands attitude had indirect effect through brand awareness to interest in using online investment applications.